Extracción y cuantificación de Teobromina existente en las semillas de cuatro variedades de cacao (theobroma cacao L) producidas en la provincia de El Oro , 2014. - Sánchez Sánchez, Juan Gabriel (2015)
Samples were taken in duplicate from the seeds of the different varieties of cocoa tested, the same as they are grown on farms in the province of Oro such as Aso-tropical, Progress, Progress Huizho and Triunfo. The following materials, container for Mixes, volumetric flask, distillation equipment, equipment to warm bath, cooker, decanting equipment, Balance brand ZHIMADZU with 0.001 mg of sensitivity, semi-industrial craftsmanship Molino, digital thermometer was used, flasks of 100 ml, funnel, magnetic stirrer, 500ml beakers, graduated pipettes, 25 ml Burette 10 ml, 250 ml Erlenmeyer flask, filter paper Whatman # 40 between the reagents used are water, 250 g sample (each variety), Ethanol, Magnesium oxide, chloroform, ethyl ether and theobromine extraction technique duplicate each cocoa variety applied.